Blood pressure variability and mortality in patients admitted with acute stroke in a tertiary care stroke centre (2016–2019): a retrospective cohort study - Sundus Sardar; Naveed Akhtar; Muhammad Zahid; Suhail Doi; Mohamed Tawengi; Rizeq F Hourani; Tamader Alyaarabi; Ahmed Adel Elsabagh; Yazan Al-Dali; Rama Ghassan Hommos; Jawaher Baraka; Abdelaziz M Tawengi; et al. (BMJ Open)
Objectives The influence of short-term variations in blood pressure (BP) in acute stroke on clinical outcomes remains uncertain. Our study explores the relationship between BP variability (BPV) from stroke admission up to 72 hours and in-hospital and 1-year mortality.Design Retrospective observational cohort study.Setting Hamad General Hospital (HGH) a tertiary care stroke centre in Qatar.Participants 2820 participants were initially included. After the exclusion of ineligible subjects, 2554 patients (82.5% male, median age 53±9 years) were included. 893 (34.96%) were from the Middle East and North Africa, 1302 (50.98%) were from South Asia, 258 (10.10%) from Southeast Asia, 9 (0.35%) were from East Asia and 92 (3.60%) were from other regions. Eligible participants were adult patients above 18 years of age who presented with acute ischaemic or haemorrhagic stroke. Excluded individuals were those younger than 18 years, had incomplete data, had transient ischaemic attack (TIA), had severe hypoglycaemia on admission (<3.3 mmol/L) or had a history of chronic kidney disease (CKD).Interventions We measured the BP every 4 hours over 3 days with a total of 18 readings from stroke admission. We then categorised BPV into five (L1–L5) and four (L1–L4) levels for systolic and diastolic BPs, respectively, and evaluated their association with mortality.Results There were increased odds of in-hospital mortality with increased systolic and diastolic variability (L2, OR 2.64, 95% CI 1.44 to 4.84; L3, OR 4.20 95% CI 2.14 to 8.24; L4, OR 10.14, 95% CI 4.93 to 20.85; L5, OR 23.18, 95%CI 10.88 to 49.37), (p=0.002 to <0.001) and (L2, OR 1.61, 95% CI 0.96 to 2.69; L3, OR 2.95, 95% CI 1.70 to 5.12 and L4, OR 8.00, 95% CI 4.49 to 14.25), (p=0.071 to <0.001), respectively. This was consistent with 1-year mortality for systolic and diastolic BPs.Conclusion In a retrospective cohort of ethnically diverse acute stroke patient population, BPV was significantly associated with both in-hospital and 1-year mortality. Further prospective research is needed to define BPV and establish interventions and management accordingly.